Knowledge, attitudes and practice among high school teachers toward students with mental disorders in Riyadh, Saudi Arabia - Alshammari, Sulaiman A.; Alenezi, Shuliweeh; Alanzan, Abdullah; AlHawamdeh, Ahmed; Alsulaiman, Omar; Alqarni, Nawaf; Aldraihem, Saad; Alsunbul, Nasser (International Journal of Research in Medical Sciences, 2022)
Background: Mental disorders are highly prevalent among adolescents, and they correlate negatively with students’ achievement, performance, and leadless school engagement and participation. School Teachers can contribute significantly to the early detection and intervention strategies for mental disorders among adolescents. This study estimates high school teachers’ knowledge, attitude, and practice toward mental disorders and determines the association between selected demographic factors. Methods: The ethical committee of King Saud University, Riyadh, Saudi Arabia, approved this cross-sectional study. Multistage random sampling was done, which included 62 male and 48 female high schools in Riyadh between August and December 2021. An Anonymous self-administered questionnaire consisting of 39-item was used for data collection. Results: A total 487 responses were received from the high school teachers, on a scale of 10 maximum score, only (60.4%) showed adequate knowledge regarding mental disorders. Even though, Majority of teachers (76.2%) show a favorable attitude toward mental disorders on a scale of 24 maximum scores. Furthermore, approximately one-third of study participants (34.4%) on a scale of 4 points maximum show good practice toward mental disorders. Conclusions: This study revealed teachers’ lack of knowledge about mental disorders with poor practice. Even though school teachers have shown favourable attitudes in most aspects toward mental disorders, implantation of the mental health literacy program is recommended to enhance the essential role of school staff in providing the needed support for promoting student mental health.